A qualitative exploration of high school dropout and retention among adolescent girls and young women (AGYW) in South Africa - Kleinhans, Crystal (Department of Public Health and Family Medicine, 2025)
In South Africa high school attrition and disengagement rates have been problematic for the past decade with adolescent girls and young women (AGYW) more likely to dropout of school than their male counterparts, especially those AGYW from socio-economically disadvantaged communities. Increased levels of education, a social determinant of health, strongly correlates with better health outcomes for youth. The disengagement and dropout of AGYW in high school is a public health concern. AGYW are at a greater risk of HIV infection and other sexually transmitted infection (STI) due to biological, cultural, religious, socio-economic and structural factors, and efforts to increase their retention and completion of high school, a protective factor, will increase the likelihood of better health outcomes in this population group. This study was a qualitative analysis of AGYW and stakeholders across five provinces from urban, semi-urban and rural districts. The transcripts were thematically analysed to explore the perceptions of and attitudes to high school completion and dropout and the factors which may contribute to either. Findings revealed that AGYW valued their high school education and associated it with future success and independence but several context specific factors on the individual, interpersonal and institutional levels influenced their retention and likelihood of dropping out of high school. An understanding of the multiple factors which influence high school dropout and retention, as indicated on the different levels of the socio-ecological model, may inform more target specific interventions to increase the retention and completion of high school of AGYW in South Africa.